2016
DOI: 10.1001/jamaophthalmol.2016.0155
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Inner and Outer Retinal Thickness in Patients Using Hydroxychloroquine Prior to Development of Retinopathy

Abstract: IMPORTANCE Retinopathy is a known risk of long-term use of hydroxychloroquine sulfate. However, whether the inner as well as outer retina are involved before retinopathy develops and whether changes in the retina might signal impending toxic effects during screening remain unknown. OBJECTIVE To determine the degree of inner and outer retinal involvement in short-and long-term use of hydroxychloroquine before the development of retinopathy. DESIGN, SETTING, AND PARTICIPANTS This retrospective medical record rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 18 publications
3
20
1
1
Order By: Relevance
“…Pasadhika and Fishman [19] also showed that a selective thinning of the inner retina can be quantified in the absence of any changes clinically visible in the fundus. Like almost all studies on the topic of hydroxychloroquine retinopathy [7, 15, 20-22], we are not able to draw any definite conclusion regarding the sequence of events associated with the disease, due to the retrospective cross-sectional design. However, our results also emphasize that the effects of long-term hydroxychloroquine are not limited to the outer retina.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…Pasadhika and Fishman [19] also showed that a selective thinning of the inner retina can be quantified in the absence of any changes clinically visible in the fundus. Like almost all studies on the topic of hydroxychloroquine retinopathy [7, 15, 20-22], we are not able to draw any definite conclusion regarding the sequence of events associated with the disease, due to the retrospective cross-sectional design. However, our results also emphasize that the effects of long-term hydroxychloroquine are not limited to the outer retina.…”
Section: Discussioncontrasting
confidence: 69%
“…Although with a sample size greater than the vast majority of studies with OCT data in hydroxychloroquine retinopathy [7-10, 13, 18, 22, 27, 28], we still recognize that stronger evidence could be derived from a larger cohort. We only included structural and functional characterization related to the central macular area, because there is a general consensus that the retinal effects of hydroxychloroquine are mainly targeted at the parafovea [1, 4].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…optische Kohärenztomografie (OCT) [13][14][15][16][17][18][19][20][21][22][23]. Die aGF sollte stan dardmäßig mit 10 Grad Durchmesser, 2 Grad Prüfabstand = 10-2 durchgeführt werden, bei asiatischen Patienten sind z.T.…”
Section: Empfohlene Ophthalmologische Untersuchungsmethodenunclassified